Refusals and Reflections : Teaching and Learning Social Justice in Qualitative Research - Campbell, Erica T.,; Shelton, Stephanie Anne, (Educational Research E-Books Online, Collection 2024., 2025)
Though qualitative research methods shape scholarship around the globe, and institutions worldwide offer qualitative coursework, there is very little explicit discussion on how to effectively teach qualitative research. Instead, a standard approach is for instructors to gain in-depth expertise in qualitative methodologies, with little or no pedagogical training. The effect is a continuous and nearly exclusive emphasis on content knowledge that undermines the preparation of novice researchers as both teachers and learners. This book works to fill that gap by offering perspectives, strategies, and applications from instructor and student perspectives, based on a semester-long class emphasizing social justice in qualitative research. This edited volume offers sections on pedagogical strategies, students' responses to and applications of those concepts, and then instructor reflections. The goal is to offer an important starting point for explicit discussions on how qualitative research might be taught and learned, in addition to how it might be thoughtfully and ethically conducted. Contributors are: Erica T. Campbell, Sun Young Gu, Kelsey H. Guy, Aimee J. Hackney, April M. Jones, Alison N. Kearley, Caran Kennedy, Amon Neely-Cowan, Allyson Pitzel, Diana Quito, Erin E. Rich, Stephanie Anne Shelton, Ashley Salter Virgin and Venus Trevae Watson. See Less